Mechanism and experimental study on preparation of high-quality vanadium nitride by one-step vacuum carbothermal reduction nitridation method. (February 2023) - Yin, Qi; Xu, Peilin; Chen, Xiumin; Liu, Li; Liu, Bo; Yang, Lianfeng; Zhao, Xiran; Sheng, Zhuo; Li, Dongqin; Yang, Bin; Xu, Baoqiang; Jiang, Wenlong; et al.
Abstract: With high hardness, high electrical conductivity, and good catalytic activity, VN is widely used in alloy materials, catalysis and electrode materials, and other fields. However, the conventional carbothermal reduction nitridation (CRN) methods are often limited by high temperatures and long reaction times. In this paper, the reaction process of vanadium trioxide one-step vacuum carbothermal reduction nitridation (VCRN) synthesis of vanadium nitride was studied by combining theoretical calculation and experimental research. The experimental results show that reducing the pressure is favorable for the V2 O3 -CRN reaction and high-quality VN was successfully synthesized under the conditions of 1473 K (300 Pa, 3 h) and the carbon mass ratio (mC /mV2O3 ) is 0.25. In addition, the reaction mechanism of V2 O3 -VCRN was elucidated by ab initio molecular dynamics (AIMD) simulations. The results show that carbon plays important role in the VCRN reaction process of vanadium trioxide. First, Carbon catalyzes the dissociation of nitrogen molecules on the surface of V2 O3 –C, which promotes the formation of the V–N bond, second is to react with O in the V2 O3 lattice and reduces V2 O3 . Highlights: This is the first time that high-quality VN is prepared by one-step vacuum carbothermal reduction nitridation (VCRN), and the method effectively reduces the reaction temperature of carbothermic reduction and nitridation. The AIMD results indicate that carbon not only plays a role in the reduction of V2 O3, but also plays a role in catalyzing the activation and dissociation of N2 during the reaction.